PARADIGMA BARU MANAJEMEN OCCUPATIONAL HEALTH NURSING DALAM PEMBELAJARAN COMMUNITY OF NURSING - Hardy MN, Syaifoel (Jurnal Keperawatan, 2012)
PARADIGMA BARU MANAJEMEN OCCUPATIONAL HEALTH NURSING DALAM PEMBELAJARAN COMMUNITY OF NURSINGNew Paradigm of Occupational Health Nursing In Community NursingSyaifoel Hardy MNPost Grad.Hospital & Healthcare Management Occupational Health Chief Nurse-Qatar Petroleum, member of American Association of Occupational Health Nurse (AAOHN), Registered Nurse of Qatar. ABSTRAKOccupational Health Nurse (OHN) adalah registered nurse yang secara independen mampu mengobservasi serta melakukan assessment terhadap kesehatan pekerja terkait dengan pekerjaan yang mereka lakukan, bahaya serta risikonya di tempat kerja (OSHA, 2009). Kompetensi yang mencakup pengetahuan, ketrampilan, training serta pengalaman registered nurses ini digolongkan dalam kemampuan mengenal dan mencegah efek yang diakibatkan oleh hazards exposure serta kepiawaian dalam menangani kasus-kasus penyakit atau luka yang disebabkan oleh kecelakaan kerja. Kecelakaan atau penyakit-penyakit sebagai dampak di tempat kerja ini perlu penanganan serius sebagaimana rekomendasi ILO (2010). Di samping itu, meningkatnya jumlah industri, di kota-kota besar, di negara-negara berkembang dan maju, menjadikan peranan Occupational Health Nurses semakin penting dan menantang di sektor industri (AAOHN, 2011). Permasalahan yang dihadapi oleh pendidikan perawat di Indonesia terkait dengan kompetensi ini adalah selama di bangku kuliah, perolehan materi Occupational Health Nursing (OHN) kurang proporsional, up to date, yang mengacu kepada basic pillars. Basic pillar ini meliputi fitness to work, health promotion and protection, management of ill health, serta health surveillance. Mengintegrasikan keempat pilar ini dalam Keperawatan Komunitas dapat dikategorikan sebagai sebuah paradigma baru pembelajaran selama di bangku kuliah. Konsep baru ini bertujuan menjadikan perawat Indonesia lebih professional serta siap dalam menghadapi era globalisasi di berbagai bidang industri di masa depan.Kata kunci : Occupational health nursing, perawatan komunitas, basic pillars, paradigma. ABSTRACTOccupational Health Nurse (OHN) is registered nurse that independently assess towards health condition of employee related to the harm and risk factor in work place (OSHA, 2009). Competence that integrating knowledge, skill, training and also experience for registered nurses, grouped in understanding capability and avoiding impact that caused by hazards exposure and skillfulled in organize case diseases or wound that caused by work accident. Accidents and diseases as a result in workplace must be seriously organized as recommended by ILO (2010). In the other hand, increase manufacture in the big city, in developing countries, make Occupational Health Nurses more important and fourmos in manufacture (AAOHN, 2011). Problems that are faced nursing education in Indonesia correlated with competence in bachelor nursing science, perolehan materi Occupational Health Nursing (OHN) unproportional, up to date, that focused on basic pillars. Basic pillar including the fitness to work, health promotion and protection, management of ill health, also health surveillance. Integration of this four components in community nursing can be catagorized as new learning paradigm in study. This new concept aims to make Indonesian nurse more professional and get ready in facing new globalization era in any other field.Key words: Occupational health nursing, community nurse, basic pillars, paradigm.